Analysis of Sociodemographic Factors on Deprresion Levels in Stroke Patients Using Structural Equating Modelling (SEM) - MJW, Endrian; Pratama Putra, Denden; Suhanda, Suhanda; Anugrah Pauji Salam, Wulan (LPPM STIKes Muhammadiyah Ciamis, 2024)
Purpose: The purpose of this study is to analyze the sociodemographic factors that affect the level of depression in stroke patients. Methods: This research method employs a Prospective Cohort approach conducted over approximately 3 months. The population and sample in this study consist of 40 respondent stroke patients in the Mawar Ward of RSUD Ciamis. Sampling was carried out using the Purposive Sampling technique. Data collection was conducted using a questionnaire assessing the level of depression using the HDRS assessment with the Structural Equating Modelling (SEM) method. Results: This research was conducted from March to May 2023. The research results from 40 respondents revealed that 12 individuals experienced depression, with 8 having mild depression, 3 with moderate depression, and 1 with severe depression. The most dominant sociodemographic factors were age and educational level, with education obtaining an R-square value of 0.198 and age 0.032. Conclusions: The conclusion drawn from this research is that sociodemographic factors influencing the level of depression in stroke patients are age and educational level.